Plant-based subsistence strategies and development of complex societies in Neolithic Northeast China: Evidence from grinding stones. (June 2016) - Liu, Li; Duncan, Neil A.; Chen, Xingcan; Ji, Ping
Abstract: In China, grinding stones (mainly slabs and elongate handstones) first appeared during the Upper Paleolithic period, and were one of the dominant tool types in many early Neolithic sites. Grinding stones were primarily used for processing plant foods and other materials. They gradually disappear in the archaeological record after 5000 BCE in the Yellow River region at the time when millet-based agriculture may have intensified. However, grinding stones were continuously used by people throughout the entire Neolithic period in the Liao River region of Northeast China. The different trajectories in food processing methods (with or without grinding stones) in the two regions are likely related to diverse types of plants exploited; and we need to understand what plants were involved. By employing residue (starch and phytoliths) and usewear analyses, this study investigates the functions of grinding stones recovered at the Baiyinchanghan site in the Liao River region, dating to three successive Neolithic cultures (Xinglongwa, Zhaobaogou, and Hongshan) from ca. 5800–3000 BCE. The results suggest that the people utilized a broad-spectrum subsistence strategy throughout the entire Neolithic, using various wild, cultivated, and domesticated plants, including tubers/roots, cereals, beans, and nuts. The earliest domesticates in the Xinglongwa period include millets and Job's tears. Rice may have been introduced to the region for the first time during the Hongshan period, coinciding with the rise of regional elite and intensified interactions with other Neolithic cultures in the south. This study sheds new light on the plant-use strategies of the grinding-stone users who developed complex societies in the Neolithic Liao River region. Highlights: Revealing a broad-spectrum subsistence strategy in Neolithic NE China Ten plant taxa were identified based on starch and phytolith analyses. Job's tears was an important crop throughout the Neolithic period in NE China. Rice may have been adapted during the fourth millennium BC in the Liao River region. The introduction of rice coincided with intensified interregional interactions.